Morphometric Wings Similarity among Sylvatic and Domestic Populations of Triatoma infestans (Hemiptera: Reduviidae) from the Gran Chaco Region of Paraguay - Rojas De Arias, Antonieta (2017)
Despite sustained efforts for eliminating Triatoma infestans, reinfestation still persists in large part of the endemic area of Chagas disease from the Gran Chaco region. Sylvatic T. infestans populations seem to threat success of control programs of domestic T. infestans. In this study, we analyzewhether T. infestans collected after a community-wide spraying were survivors or were immigrants from elsewhere using geometric morphometric tools. We used 101 right wings of female T. infestans captured before and after intervention program carried out in 12 de Junio and Casuarina, villages from Paraguayan Chaco, and in Puerto Casado during presprayed collection. There were no significant differences in wing size of domestic T. infestans between pre- and postspraying populations, and between domestic and sylvatic ones.When shape variables originating from postintervention individuals from 12 de Juniowere introduced one by one into a discriminant analysis, the greatest weight (53%)was allocated to the sylvatic group. Furthermore, from the prespraying population, 25% were reallocated as postintervention individuals. Only 11% of the insects were reassigned to other groups Puerto Casado and Casuarina. These results suggest that postspraying individuals appear to have different origins. Half of the postspraying individuals from 12 de Junio were similar to the sylvatic ones and 25% of these were similar to those captured in the prespraying period. This remarkable morphometric wings similarity between sylvatic and domestic populations is new evidence suggesting that they could be highly related to each other in the Paraguayan Chaco; human-fed bugs from sylvatic area also support this.